2021
DOI: 10.1186/s13023-021-01784-7
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of second-tier tests in newborn screening for the detection of vitamin B12 related acquired and genetic disorders: results on 258,637 newborns

Abstract: Background Alteration of vitamin B12 metabolism can be genetic or acquired, and can result in anemia, failure to thrive, developmental regression and even irreversible neurologic damage. Therefore, early diagnosis and intervention is critical. Most of the neonatal cases with acquired vitamin B12 deficiency have been detected by clinical symptoms and only few of them trough NBS programs. We aim to assess the usefulness of the second-tier test: methylmalonic acid (MMA), methylcitric acid (MCA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…In our data, there was a wide, overlapping range of C3 concentrations in both genetic and acquired vitamin B12 deficiency cases, with some of the highest values found in newborns determined to be unaffected. Two recent papers substantiate our finding that C3 is not a specific marker for disorders of propionate metabolism [ 13 , 33 ]. Within our data, there was also significant overlap in the C3/C2 values between IEM and false positive cases, which differed from the findings of other groups, who have suggested that C3/C2 provides better sensitivity and is more frequently high in genetic rather than acquired conditions [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our data, there was a wide, overlapping range of C3 concentrations in both genetic and acquired vitamin B12 deficiency cases, with some of the highest values found in newborns determined to be unaffected. Two recent papers substantiate our finding that C3 is not a specific marker for disorders of propionate metabolism [ 13 , 33 ]. Within our data, there was also significant overlap in the C3/C2 values between IEM and false positive cases, which differed from the findings of other groups, who have suggested that C3/C2 provides better sensitivity and is more frequently high in genetic rather than acquired conditions [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…Two recent papers substantiate our finding that C3 is not a specific marker for disorders of propionate metabolism [ 13 , 33 ]. Within our data, there was also significant overlap in the C3/C2 values between IEM and false positive cases, which differed from the findings of other groups, who have suggested that C3/C2 provides better sensitivity and is more frequently high in genetic rather than acquired conditions [ 33 , 34 ]. Our data also show that the methylmalonic acid (MMA) concentration obtained on the second-tier test does not help to distinguish an IEM from acquired disease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Methylmalonic acid, methylcitric acid and homocysteine are widely known biomarkers of genetic conditions leading isolated or combined MMA and HCY, or PA. However, elevations of methylmalonic acid, methylcitric acid and homocysteine can also be the result of secondary alterations, such as secondary vitamin B12 deficiency ( Pajares et al, 2021 ). Therefore the second-tier test of methylmalonic acid, methylcitric acid and homocysteine is necessary to differentially diagnose the secondary vitamin B12 deficiency when we screening for MMA and HCY.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkly, CblC showed an incidence of 1: 32,271, making this disease one of the most common inherited metabolic diseases in the Italian population, with one of the highest prevalences in the world. The reported incidence in Portugal was 1:85,000 [ 22 ], in Spain and, in the US, 1:100,000 [ 25 , 26 ], while a pilot study in Beijing, China showed the worldwide highest incidence of 1:11,730 [ 27 ]. Defining the mutation spectrum in CblC cases was beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%